Gearing service quality into public and private hospitals in small islands: Empirical evidence from Cyprus - Arasli, Huseyin; Ekiz, Erdogan Haktan; Katircioglu, Salih Turan (Emerald Group Publishing, 2008)
Purpose - The purpose of this research is to develop and compare some determinants of service quality in both the public and private hospitals of Northern Cyprus. There is considerable lack of literature with respect to service quality in public and private hospitals. Design/method/approach - Randomly, 454 respondents, who have recently benefited from hospital services in Famagusta, were selected to answer a modified version of the SERVQUAL Instrument. The instrument contained both service expectations and perceptions questions. Findings - This study identifies six factors regarding the service quality as perceived in both public and private Northern Cyprus hospitals. These are: empathy, giving priority to the inpatients needs, relationships between staff and patients, professionalism of staff, food and the physical environment. Research results revealed that the various expectations of inpatients have not been met in either the public or the private hospitals Research implications/limitations - At the micro level, the lack of management commitment to service quality in both hospital settings leads doctors and nurses to expend less effort increasing or improving inpatient satisfaction. Hospital managers should also satisfy their employees, since job satisfaction leads to customer satisfaction and loyalty. Additionally, hospital administrations need to gather systematic feedback from their inpatients, establish visible and transparent complaint procedures so that inpatients' complaints can be addressed effectively and efficiently. Originality/value - The hospitals need to organize training sessions based on the critical importance of service quality and the crucial role of inpatient satisfaction in the health care industry. Future studies should include the remaining regions in Cyprus in order to increase research findings' generalizability. Additionally, including other dimensions such as hospital processes and discharge management and co-ordination may provide further insights into understanding inpatients' perceptions and intentions
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Cyprus, Private hospitals; Public sector organizations, Patients, Customer services quality, Hospitals, Hospitals; Private - organization & administration, Hospitals, Public - organization & administration, Quality Indicators, Health Care - organization & administration; Quality Assurance, Health Care - organization & administration, Health care delivery, Customer services, Quality of service, Statistical analysis, Studies